(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2020)
Working capital management is important because of its impact on the owner’s wealth, shown as the economic value of the enterprise, which is the result of interdependence of profitability and risk. Enterprises that invest more in working capital can expect lower levels of business risk, but unfavorable influences on profitability levels, and vice versa. Considering the importance of efficient working capital management, the main objective of this paper is to examine the relationship between working capital management and the profitability of Croatian small and medium-sized manufacturing enterprises (SMEs) and to provide empirical evidence on the effects of working capital management on the level of profitability of such enterprises. The panel analysis was used to examine the impact of accounts receivable, inventories, accounts payable, company size, sales growth, GDP growth and inflation rate on the profitability of Croatian manufacturing SMEs over a six-year period (2010-2015). The model confirmed the impact of inventories, accounts payable, and sales growth on the firm’s profitability level, while the effect of accounts receivable and company size on the company’s profitability was not confirmed, partially confirming the underlying working hypothesis. The control variables GDP and inflation were not statistically significant. It was found that manufacturing companies can increase their profitability by avoiding late payments to suppliers and by increasing inventory turnover, i.e., by holding inventory for as little time as possible. Moreover, businesses can increase their profitability by boosting sales growth.